Effectiveness of Combined Acupuncture Therapy and Turmeric (Curcuma longa Linn) on Blood Protein Profile in Osteoarthritis Patients - Kusumawati, Heni Nur; Prasetya, Hanung; Nugraha, Nurtama Aditya (Indonesian Journal of Medicine, 2025)
Background: Osteoarthritis (OA) is a degenerative disease of the joints that commonly occurs in the hands, waist, a. nd knees. One of the efforts to control OA is with acupuncture. This study aims to analyze the effectiveness of the combination of acupuncture and turmeric herbs on reducing the levels of total protein, albumin, and globulin in OA patients. Subjects and Method: The Randomized Controlled Trial (RCT) study was conducted at Redy Clinical Laboratory in August 2024. A total of 50 patients with OA were divided into two groups: (1) Intervention group of combination of acupuncture and turmeric herbs (n= 25); and (2) The control group was given acupuncture (n=25). The dependent variables are total protein, albumin, and globulin. The independent variable was a combination of acupuncture and turmeric herbs. The difference in the average increase in protein, albumin, and globulin levels in each group was analyzed using the Independent test. Results: The average protein level in the combination group of acupuncture therapy and turmeric herbs (Mean= 8.40; SD= 0.27) was higher than the control group (Mean= 7.74; SD= 0.33), and this result was statistically significant (p <0.001). The average albumin level in the combination group of acupuncture therapy and turmeric herbs (Mean= 5.07; SD= 0.49) was higher than the control group (Mean= 4.84; SD= 0.66), but this result was statistically insignificant (p= 0.156). The average globulin levels in the combination group of acupuncture therapy and turmeric herbs (Mean= 3.41; SD= 0.88) were higher than the control group (Mean= 3.17; SD= 0.65), but this result was statistically insignificant (p = 0.280). Conclusion: The combination of acupuncture therapy and turmeric herbs is effective in increasing total protein, albumin, and globulin levels in OA patients.